A methodology to assess drought management as applied to six European case studies. Issue 2 (4th March 2017) - Urquijo, Julia; Pereira, David; Dias, Susana; De Stefano, Lucia
Abstract: The improvement of future responses to drought requires evaluating past management practices. This article presents a methodology to assess drought management through the analysis of six key policy dimensions. It uses a qualitative approach that combines different sources of information, including both factual data and stakeholders' perceptions. The assessment is based on a six-case study in Europe having different spatial scales and characteristics, to capture the context-specific nature of response to drought. The results of the assessment help analyze drought management from a risk-management perspective as well as to identify key policy gaps and recommendations.